2006
DOI: 10.1073/pnas.0511319103
|View full text |Cite
|
Sign up to set email alerts
|

Identification of proangiogenic genes and pathways by high-throughput functional genomics: TBK1 and the IRF3 pathway

Abstract: A genome-wide phenotype screen was used to identify factors and pathways that induce proliferation of human umbilical vein endothelial cells (HUVEC). HUVEC proliferation is a recognized marker for factors that modulate vascularization. Screening ''hits'' included known proangiogenic factors, such as VEGF, FGF1, and FGF2 and additional factors for which a direct association with angiogenesis was not previously described. These include the kinase TBK1 as well as Toll-like receptor adaptor molecule and IFN regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
84
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 28 publications
(41 reference statements)
2
84
0
Order By: Relevance
“…It is activated by infection of a number of viruses, including SV40, Ebola, influenza, Sendai, and human Our results suggest that TBK1 participates in cell proliferation and cell survival by regulating Akt. In fact, TBK1 has been reported to promote tumor growth and proliferation of HUVECs (27). Hasan et al (28) reported that TRIF/TBK1 regulates phosphorylation of the cell cycle inhibitor p27 kip1 and proteasome degradation.…”
Section: Discussionmentioning
confidence: 99%
“…It is activated by infection of a number of viruses, including SV40, Ebola, influenza, Sendai, and human Our results suggest that TBK1 participates in cell proliferation and cell survival by regulating Akt. In fact, TBK1 has been reported to promote tumor growth and proliferation of HUVECs (27). Hasan et al (28) reported that TRIF/TBK1 regulates phosphorylation of the cell cycle inhibitor p27 kip1 and proteasome degradation.…”
Section: Discussionmentioning
confidence: 99%
“…CRMP1 is a suppressor of tumor cell invasion of the local stroma and might be a functional modulator of the Wnt signaling pathway in vivo (17,18). As the trigger of TBK-1 pathway, TBK1 is important for tumor angiogenesis and tumor-associated microvascular inflammation and expressed at significant levels in many solid tumors (19,20). A recent study has demonstrated that SEPT7 could function in gliomagenesis and in the suppression of glioma cell proliferation (21).…”
Section: Discussionmentioning
confidence: 99%
“…This protein is expressed in various rodent tissues such as stomach, small intestine, lung, testis, skin, brain, heart, kidney, spleen, thymus, and liver (Pomerantz & Baltimore 1999) and appears to be activated by phorbol esters, tumor promoters and growth factors (Tojima et al 2000). The known functions of TBK1 are related with the development of the innate antiviral response (Harris et al 2006) and with tumor angiogenesis (Korherr et al 2006). In the present report, we confirmed that TNF-a is directly associated with the induction of TBK1 in liver, first by showing that in OZRs large hepatic TBK1 levels coexist with increased levels of TNF-a and second by showing that rats infused by 4 h with TNF-a displayed large levels of association of this enzyme with the IR.…”
Section: Discussionmentioning
confidence: 99%